To solve this system of equations, we can use substitution or elimination method.
First, let's solve for y in the first equation:
y = -3/2x - 2
Now, we can substitute this expression for y into the second equation:
2x - (-3/2x - 2) = -5
2x + 3/2x + 2 = -5
(4x + 3x + 4)/2 = -5
7x + 4 = -10
7x = -14
x = -2
Now that we have found the value of x, we can substitute it back into the first equation to find the value of y:
y = -3/2(-2) - 2
y = 3 + 2
y = 5
Therefore, the solution to the system of equations is x = -2 and y = 5.
y= -3/2x -2, 2x-y=-5
1 answer